Design and implementation of a patient-derived surgical goal setting program for elective lumbar spine surgery - Martin, Sheyne; Caras, Andrew J.; Johnson, Kristen; Allen, Crystal S.; Bradbury, Heather B.; Holloway, Kathryn L.; Verma, Ketan (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionPatient-reported outcomes are widely used to measure surgical success in patients undergoing elective lumbar spine surgery. However, unique goals created by patients may provide a more accurate and individual representation of surgical success. We hypothesize that creation of a patient-derived goal-setting program, and analysis of such goals using an interactive visual dashboard, may provide unique insight into factors important to patients undergoing elective lumbar spine surgery.MethodsCreation of a visual dashboard was performed with key stakeholders (neurosurgeons, advanced practice providers and informaticists). Patient derived functional and pain goals were set and documented prior to surgery. Goal achievement and surgery satisfaction were collected at primary (6 weeks, 3 months) and secondary (6, 12, ≥12 months postoperatively) endpoints. Schema were created to organize words used in patient-identified goals into specific trends for analysis. Data were analyzed using Chi-square test for statistical significance.ResultsA real-time visual electronic dashboard was successfully implemented, and used throughout the study. A total of 158 patients underwent elective lumbar spine surgery, of which 75 (47%) participated in the goal-setting program. Most patients identified a pain goal of ≥75% reduction (X2 = 32.000, p < 0.001). The most common word used in functional goals was “able.” The most common word used in pain goals was “improvement.” Functional goals were separated into three schemata: “Change Talk,” (60%) “Activity,” (20%) and “Symptoms” (20%). Pain goals were separated into two schemata: “Symptoms” (64%) and “Change Talk” (36%). At 3 months postoperatively, 86% of patients were satisfied with surgery although only 39.1% had achieved their functional goals and 67.9% had achieved their pain goals.DiscussionThe study illustrates the implementation, use and interpretation of a real-time visual dashboard in a unique, patient-derived goal setting program for patients undergoing elective lumbar spine surgery. Patient satisfaction with surgery may not directly correlate with functional and pain goal achievement. Less than half of the eligible total population participated, underscoring the difficulty of long-term compliance. Expanded integration of this program may allow improved understanding of unique factors important topatients, as they undergo elective lumbar spine surgery.